2013
DOI: 10.5455/jbh.20130325033852
|View full text |Cite
|
Sign up to set email alerts
|

Does Religiosity Influence Attitude to Mental Illness? and #8211; A survey of Medical students in a Nigerian University.

Abstract: Background: The benefits of religiosity in mental health has been documented in extant literature. However the relationship between religiosity and medical students' attitude to mental illness has not been explored by previous studies. This study aimed to determine the relationship between religiosity and the attitude of medical students in a Nigerian university to mental illness. Methods: Fifth year medical students completed a sociodemographic and career choice questionnaire, Duke University religiosity inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Positive attitudes were prevalent among the clergy towards people with mental disorders in Nigeria (Iheanacho et al, 2016(Iheanacho et al, , 2018. Adelufosi, Abayomi, Oyewole, & Ayankola, (2013) also explained that social contact between frequent attendees in religious activities with people who have mental disorders, may promote some element of compassion and sympathy, resulting in some positive attitudes towards mental disorders. This is possibly because religion promotes compassion for individuals with health problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive attitudes were prevalent among the clergy towards people with mental disorders in Nigeria (Iheanacho et al, 2016(Iheanacho et al, , 2018. Adelufosi, Abayomi, Oyewole, & Ayankola, (2013) also explained that social contact between frequent attendees in religious activities with people who have mental disorders, may promote some element of compassion and sympathy, resulting in some positive attitudes towards mental disorders. This is possibly because religion promotes compassion for individuals with health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional healers sometimes called 'witch doctors' have always been of interest to medical doctors and other allied professionals in Nigeria, even though studies have shown that medical professionals exhibit negative attitudes towards traditional medicine (Adelufosi et al, 2013;Offlong, 1999). However, many studies have indicated that native and spiritual healers could be used as effective agents in mental health in Nigeria (Adelekan et al, 2001;Agara et al, 2008;Iheanacho et al, 2016Iheanacho et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation